Phosphorylation and Stabilization of PIN1 by JNK Promote Intrahepatic Cholangiocarcinoma Growth. Issue 5 (15th September 2021) - Lepore, Alessio; Choy, Pui Man; Lee, Nathan C.W.; Carella, Maria Annunziata; Favicchio, Rosy; Briones‐Orta, Marco A.; Glaser, Shannon S.; Alpini, Gianfranco; D'Santos, Clive; Tooze, Reuben M.; Lorger, Mihaela; Syn, Wing‐Kin; et al.
Abstract : Background and Aims: Intrahepatic cholangiocarcinoma (ICC) is a highly aggressive type of liver cancer in urgent need of treatment options. Aberrant activation of the c‐Jun N‐terminal kinase (JNK) pathway is a key feature in ICC and an attractive candidate target for its treatment. However, the mechanisms by which constitutive JNK activation promotes ICC growth, and therefore the key downstream effectors of this pathway, remain unknown for their applicability as therapeutic targets. Our aim was to obtain a better mechanistic understanding of the role of JNK signaling in ICC that could open up therapeutic opportunities. Approach and Results: Using loss‐of‐function and gain‐of‐function studies in vitro and in vivo, we show that activation of the JNK pathway promotes ICC cell proliferation by affecting the protein stability of peptidyl‐prolyl cis‐trans isomerase NIMA‐interacting 1 (PIN1), a key driver of tumorigenesis. PIN1 is highly expressed in ICC primary tumors, and its expression positively correlates with active JNK. Mechanistically, the JNK kinases directly bind to and phosphorylate PIN1 at Ser115, and this phosphorylation prevents PIN1 mono‐ubiquitination at Lys117 and its proteasomal degradation. Moreover, pharmacological inhibition of PIN1 through all‐trans retinoic acid, a Food and Drug Administration–approved drug, impairs the growth of both cultured and xenografted ICC cells. Conclusions: Our findings implicate the JNK‐PIN1 regulatory axis as a functionally important determinant for ICC growth, and provide a rationale for therapeutic targeting of JNK activation through PIN1 inhibition.